LATERAL ORGAN BOUNDARIES DOMAIN 25 functions as a key regulator of haustorium development in dodders. Issue 4 (27th May 2021) - Jhu, Min-Yao; Ichihashi, Yasunori; Farhi, Moran; Wong, Caitlin; Sinha, Neelima R
Abstract: Parasitic plants reduce crop yield worldwide. Dodder ( Cuscuta campestris ) is a stem parasite that attaches to its host, using haustoria to extract nutrients and water. We analyzed the transcriptome of six C. campestris tissues and identiﬁed a key gene, LATERAL ORGAN BOUNDARIES DOMAIN 25 ( CcLBD25 ), as highly expressed in prehaustoria and haustoria. Gene coexpression networks from different tissue types and laser-capture microdissection RNA-sequencing data indicated that CcLBD25 could be essential for regulating cell wall loosening and organogenesis. We employed host-induced gene silencing by generating transgenic tomato ( Solanum lycopersicum ) hosts that express hairpin RNAs to target and down-regulate CcLBD25 in the parasite. Our results showed that C. campestris growing on CcLBD25 RNAi transgenic tomatoes transited to the flowering stage earlier and had reduced biomass compared with C. campestris growing on wild-type (WT) hosts, suggesting that parasites growing on transgenic plants were stressed due to insufficient nutrient acquisition. We developed an in vitro haustorium system to assay the number of prehaustoria produced on strands from C. campestris . Cuscuta campestris grown on CcLBD25 RNAi tomatoes produced fewer prehaustoria than those grown on WT tomatoes, indicating that down-regulating CcLBD25 may affect haustorium initiation. Cuscuta campestris haustoria growing on CcLBD25 RNAi tomatoes exhibited reduced pectin digestion and lacked searching hyphae, which interfered with haustorium penetration and formation of vascular connections. The results of this study elucidate the role of CcLBD25 in haustorium development and might contribute to developing parasite-resistant crops. Abstract : Transcription factor CcLBD25 plays a pivotal role in haustorium initiation, regulating pectin digestion, and searching hyphae development during the haustorium penetration process.